2021
DOI: 10.1021/acs.joc.1c01151
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Tool Kit of Automated Flow Synthesis: Development of In-line Flash Chromatography Purification

Abstract: Recent advancements in in-line extraction and purification technology have enabled complex multistep synthesis in continuous flow reactor systems. However, for the large scope of chemical reactions that yield mixtures of products or residual starting materials, off-line purification is still required to isolate the desired compound. We present the in-line integration of a commercial automated flash chromatography system with a flow reactor for the continuous synthesis and isolation of product(s). A proof-of-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…With an in-line extraction system in hand, we envisioned a system which would eliminate a further time-consuming unit operation, product purification. Inspired by recent reports of the incorporation of the Advion puriFlash 5.250 system in a continuous flow system [ 38 ], we aimed to apply this system to our flow setup. The puriFlash system is an automated liquid chromatography purification system which is capable of purifying mixtures in a continuous fashion by using alternating sample loops and chromatography columns.…”
Section: Resultsmentioning
confidence: 99%
“…With an in-line extraction system in hand, we envisioned a system which would eliminate a further time-consuming unit operation, product purification. Inspired by recent reports of the incorporation of the Advion puriFlash 5.250 system in a continuous flow system [ 38 ], we aimed to apply this system to our flow setup. The puriFlash system is an automated liquid chromatography purification system which is capable of purifying mixtures in a continuous fashion by using alternating sample loops and chromatography columns.…”
Section: Resultsmentioning
confidence: 99%
“…However, this can be achieved by final-product purification using techniques such as multicolumn chromatography catch-and-release chromatography, simulated moving bed (SMB), crystallisation, recrystallisation and centrifugal partition chromatography (CPC). 51,54–59 Adding to scalability concerns of some of these purification methodologies, these techniques have their drawbacks; crystallization and recrystallisation usually requires semi-batch processing, catch-and-release chromatography needs automated multiple columns switching and the SMB chromatography operation is technically complex and it uses expensive absorbents. 12,51,60 The application of various downstream continuous flow processing strategies examples are reviewed herein.…”
Section: Continuous-flow Downstream Processingmentioning
confidence: 99%
“…Thomson et al 55 reported an inline flash chromatography system that can be utilized for continuous flow synthesis and the isolation of products (Fig. 16).…”
Section: Continuous-flow Downstream Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Purification of fine chemicals by preparative chromatography is a routine task in the organic chemistry laboratory. While numerous advances have been made since Still’s seminal publication on flash column chromatography, especially in the context of automated systems using prepackaged columns and UV detectors, the classic approach is still in widespread use in research laboratories around the world. The low-tech nature also means that the technique is widely accessible and may be carried out using standard laboratory equipment. Additionally, and of special importance in this context, the process is highly educational, with an exposed setup in which all internal workings are observableunlike that of an HPLC system, which typically operates in a much more “black box” manner. , As a consequence of this, the described chromatographic purification experiment will also be helpful for preparing students for more advanced practices and theory related to chromatography through practical experience.…”
Section: Introductionmentioning
confidence: 99%